Impact of Transformational Leadership Style on Achieving Digital Transformation Strategy a Field Study on Employees of the General Electricity Company - Emran, Hasan Abdulsalam Ali; Elhony, Fathia . M. (East Asian Journal of Multidisciplinary Research, 2024)
The study aims to explore the impact of transformational leadership style on achieving the digital transformation strategy, focusing on a sample of employees at the General Electricity Company. A questionnaire served as the primary data collection tool, with 348 questionnaires distributed to participants. Out of these, 298 valid responses were retrieved for analysis. The findings reveal a significant positive impact of the transformational leadership style on achieving the digital transformation strategy, particularly in terms of idealized influence and inspirational motivation. The study also highlights the importance of having a clear vision, mission, and strategic digital goals as a foundation for initiating the digital transformation journey. This underscores the need for a digital leader, emphasizing leadership as a critical factor in determining the successful implementation of digital transformation.